-4
$\begingroup$

My question is as follows: See image of TI-89 output Use induction to prove the following formula for $n \geq 2$

Solution (what I have tried so far):

Base case: $n=2$

RHS: $\int \sin^2xdx = \int 1/2 (1-\cos(2x))dx$

LHS: $\dfrac{-1}{2} \cos x \sin x + \dfrac{2-1}{2} \int dx$

RHS = LHS so base case holds (supposed to be but I haven't worked it out).

Induction Hypothesis (assume true for $n = k$): $\int \sin^kx dx = \dfrac{-1}{k} \cos x(\sin^{k-1}x) + \dfrac{k-1}{k} \int(\sin^{k-2}x)dx$

Induction Step: ($n = k + 1$) requires $\int (\sin^{k+1}x) dx = \dfrac{-1}{k+1} \cos x(\sin^kx) + \dfrac{k}{k+1} \int (\sin^{k-1}x)dx$

So, $\int (\sin^{k+1}x) dx = \in (\sin^kx) dx + \int \sin x dx$

$\endgroup$
  • $\begingroup$ For the base case using your method of writing $\sin^2(x)$ as $\frac12(1-\cos(2x)$, continue by writing $\int\frac12(1-\cos(2x))dx$ as $\int\frac12dx-\int\cos(2x)dx$. Then the "$\int\frac12dx$" pairs off with the "$\frac{2-1}{2}\int dx$". So you just need to prove that $\int\cos(2x)dx=\frac{-1}2\cos(x)\sin(x)$. To do this, evaluate $\int\cos(2x)dx$ by taking a substitution $u=2x$, then rewrite the resulting answer (which looks like $\sin(2x)$) in terms of $\sin(x)$ and $\cos(x)$. $\endgroup$ – user1729 Apr 19 '18 at 14:42
  • $\begingroup$ (Of course, you don't need to base case if you use the method in my answer...but anyway...) $\endgroup$ – user1729 Apr 19 '18 at 14:42
0
$\begingroup$

Proof by induction is not necessary here. Suppose $n\geq 2$. First, think of $\sin^n(x)$ as a product $\sin^{n-1}(x)\cdot\sin(x)$. We can then use integration by parts: Take $f'=\sin(x)$ and $g=\sin^{n-1}(x)$ where the rule is $\int f'g=fg-\int fg'$.

This gives the following: $$ \begin{align*} \int\sin^n(x)dx &=-\cos(x)\sin^{n-1}(x)+(n-1)\int\cos^2(x)\sin^{n-2}(x)dx\\ &=-\cos(x)\sin^{n-1}(x)+(n-1)\int(1-\sin^2(x))\sin^{n-2}(x)dx\\ &=-\cos(x)\sin^{n-1}(x)+(n-1)\int\sin^{n-2}(x)dx-k\int\sin^{n}(x)dx\\ \Rightarrow n\int\sin^n(x)dx&=-\cos(x)\sin^{n-1}(x)+(n-1)\int\sin^{n-2}(x)dx\\ \Rightarrow\int\sin^n(x)dx&=-\frac{1}{n}\cos(x)\sin^{n-1}(x)+\frac{n-1}{n}\int\sin^{k-1}(x)dx \end{align*} $$ as required.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.